El pedestal erróneo para un prócer. Antonio Nariño y la revolución neogranadina (Tzintzun, Revista de Estudios Históricos, 2016)
Antonio Nariño, who is known as the forefather of Colombian independece, was elevated to the highest standing of revolutionary heroes by patriotic historiography. This article seeks to reexamine certain aspects of his public life which were important moments during the revolution in the 1810s. These aspects help us to understand better this event by stripping the fatalistic illusion in which he has been vested.
Keywords: Colombia; revolution; independence; nation; Antonio Nariño